Exploring biomedical and traditional care pathways for people with psychosis in Karachi, Pakistan - Khan, Zahra; Qureshi, Onaiza; Pasha, Aneeta; Majid, Osama; Saleem, Saniya; Fearon, Pasco; Shaikh, Madiha (Frontiers in Psychiatry, 2023)
Background Psychosis is known to have an adverse impact on an individual’s quality of life, social and occupational functioning. A lack of treatment options for psychotic disorders such as schizophrenia contributes to adverse outcomes for individuals. A significant proportion of people with psychosis consult both formal and traditional routes of care. This warrants a need to explore perceptions around treatment options provided by diverse care providers, as the identification of avenues for support can improve psychiatric, alternative treatment and social outcomes. Methods Focus groups discussions (FGDs) and in-depth interviews (IDIs) were used. Interactive Research and Development (IRD) research staff conducted 20 IDIs and 2 FGDs to obtain information about the perspectives, treatment pathways and experiences of individuals with psychosis, their caregivers, and service providers. Questions for clinician care providers and faith healers revolved around perceptions of psychosis, service users’ background, subject knowledge and treatment, feedback and referral mechanisms, and promotion of services. A thematic analysis was used to analyze the interviews and coding was conducted on NVivo. Results The results were categorized into five themes: perception of psychosis, experience of seeking/receiving care, assessment and diagnosis methods, promotion of services, and living with psychosis. Across service providers and patients, there was a wide variety of causes attributed to psychosis, and an overall lack of awareness regarding severe mental health conditions from both formal and informal care-providers. Biomedical treatment received mixed reviews, while some reported it as beneficial, the limited number of institutes and clinicians to cater for patients, stigma within society and care providers, the burden of caregiving, and misinformation from faith healers were all significant barriers to treatment. Conclusion The results highlight the use of traditional healing practices for psychosis in Pakistan, which, coupled with inadequate referral mechanisms, present an opportunity to bridge the treatment gap between clinical and traditional healing practices through integration of treatment within community structures and systems. Better awareness of psychosis and its treatment methods, alongside interventions that reduce stigma could help facilitate help-seeking behavior and reduce the burden of caregiving.